The embodied image : imagination and imagery in architecture - Pallasmaa, Juhani (Chichester : John Wiley & Sons, 2011)
Architecture is usually analysed and taught as a discipline that articulates space and geometry, but the mental impact of architecture arises significantly from its image quality that integrates the various aspects and dimensions of experience into a singular, internalised and remembered entity.
Introduction -- Image in contemporary culture -- Language, thought and image -- The many faces of the image -- The anatomy of the poetic image -- The architectural image.
Includes bibliographical references and index.
Keywords: Architecture -- Aesthetics; Art and architecture; Architecture -- Themes, motives; Architecture -- Philosophy